Małżeństwo i rodzina w Polsce piastowskiej – analiza historyczno prawna - Lis, Artur (Przegląd Prawno-Ekonomiczny, 2013)
Streszczenie dostępne wyłącznie w języku angielskim: The nature of the family in medieval Poland was varied depending on the social group, wealth, ownership situation, tradition, region, and many other factors. The most important functions of the family were procreative, economic, educational, cultural and safety. It should be emphasized that the needs of people in the Middle Ages were implemented mainly in the family. It provided suport for each of its members and assured safety.